KECEMASAN DAN DUKUNGAN KELUARGA BERHUBUNGAN DENGAN CARA PEMILIHANPERSALINAN DI RSAD WIRA BHAKTI MATARAM TAHUN 2018 - Hermawati (SANGKAREANG, 2020)
Giving birth in Army Hospital (RSAD) of Mataram in 2016 from 1206 number of deliveries, giving birth by Section Caesarea achieved 566 (46.93%). Some of giving birth by Section Caesarea is not a must medically. Result of study by Basalamah and Galuardi found most of mothers said that there is anxiety pain when delivered for first giving birth (primigravida) second or third and so forth. Mother who chose giving birth by Section Caesarea got support from her husband because he does pity to see his wife got pain when giving birth. Interview toward 6 husbands when he accompanied her wife control, all of them support their wives giving birth by Section. This study aimed to know the relationship between anxiety and family’s support toward choosing of giving birth method at RSAD Wirabhakti of Mataram in 2018. This study is observational analytic by cross sectional. Population of the study is all delivery mothers from January up to October 2018 in the amount of 999 respondents. There are 91 respondents taken as samples by accidental sampling technique. Statistic test by Chi Square test. Result of the study showed by Chi Square test got p value = 0.000 < α 0.05. It meant there was a significant relationship between anxiety and pain toward choosing of giving birth method at RSAD Wirabhakti of Mataram in 2018.Data analyzed by Chi Square test gotp value 0.000 < α 0.05. It meant that there was a significant relationship between family’s support and choosing of giving birth method at RSAD Wirabhakti of Mataram in 2018. Family’s support gave affect 30.15 bigger to choose giving birth method by Section Caesarea than normal delivery at RSAD Wirabhakti of Mataram in 2018. Based on the conclusion, it is suggested to the Head of RSAD Wirabhakti of Mataram to design intensive program to delivery mothers to intervention anxiety and family’s support in choosing normal giving birth method so that it can be a guideline for attendant at delivery room in giving motivation to delivery mothers and families in choosing normal giving birth method.